THE CONCEPT OF MANAGEMENT ACCOUNTING BASED ON PRODUCT MOVEMENT AND COST INCREASE IN CONTROLLING SYSTEM - TATYANA Karpova (Учёт. Анализ. Аудит)
The article describes the main features of the management accounting concept based on the product movement at different stages of the manufacturing process by cost centers. The key element of the concept is the process of calculating “basic” and additional resources, intermediate and final products in order to managecosts following their increase in the course of manufacturing operations set by technology and production process organization.The article also focuses on building the costing process when the involvement in production occurs during all technological processes of producing goods and providing services. The use of such an approach in product and functional cost accounting, as well as in calculation of intermediate and final products creates an opportunity to choose within the controlling system the method to monitor both the level of information support for modern operational, tactical and strategic management decisions and their immediate implementation.